Increasing the Data Transmission Robustness in Wsn Using the Modified Error Correction Codes on Residue Number System - Sachenko, Anatoliy; Zhengbing, Hu; Yatskiv, Vasyl (Elektronika ir Elektrotechnika, 2015)
The WSN standard IEEE802.15.4 basically uses the unlicensed frequency of 2,4 GHz for data transmission in a variety of devices, standards and applications: IEEE802.11, Bluetooth and etc. In this paper we proposed modified correction codes – based on Residue Number System – to improve the data transmission robustness in WSN. These codes are characterized by high correction characteristics as well as the simplified coding procedure. There are given examples, and circuits of the both coder and decoder are designed for such modified correction codes using the Residue Number System and CPLD. DOI: http://dx.doi.org/10.5755/j01.eee.21.1.6657